RANCANGAN SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI KANTOR KOREM GAPU 042 JAMBI - Mulyadi - (JURNAL AKADEMIKA)
The purpose of this study are as follows: Analyze and study the information systems that run on Cooperative Korem Gapu 042, identify the problems that occur in the Cooperative Korem Gapu 042, Designing information systems services savings and loans cooperatives Skorem Gapu 042 computerized To apply a good information system in order to develop cooperative Korem Gapu 042. the system applied in the Cooperative Office Korem 042 Gapu Jambi still be said to be due to manual data processing still use manual transactions. By using the system to manual it will display an indication of the occurrence of errors in data processing of transactions. Given pentinganya implementation of information systems, either in a cooperative, needed a better development by changing the manual system to a computerized system.